Churchill - Jenkins, Roy, 1920-2003. (London : Pan Books, 2002)
Provides a glimpse into the extraordinary life of Britain's greatest prime minister, recreating his many accomplishments, trials, and tribulations throughout his life that contributed to his success.
pt. 1. A brash young man 1874-1908 -- pt. 2. The glow-worm glows : the morning was golden 1908-1914 -- pt. 3. The noontide was bronze 1914-1918 -- pt. 4. Hesitant afternoon sunshine 1919-1939 -- pt. 5. The saviour of his country and the light of the world? 1939-1945 -- pt. 6. Was the evening leaden? 1945-1965.
Includes bibliographical references (pages 953-957) and index.
Koleksi sumbangan Tun (Dr.) Ahmad Sarji Abdul Hamid.
Keywords: Churchill, Winston, -- 1874-1965.; Prime ministers -- United Kingdom -- Biography; Great Britain -- Politics and government -- 20th century